2023
DOI: 10.7759/cureus.34747
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiological, and Lung Function Characteristics of Post-tuberculosis Bronchiectasis: An Experience From a Tertiary Care Center in India

Abstract: IntroductionAmong chronic respiratory diseases, bronchiectasis is one of the important causes of mortality and morbidity in developing countries. ObjectiveThis study aimed to assess the clinical, radiological, microbiological, and pulmonary function profiles of adult patients with post-tubercular bronchiectasis. MethodsWe enrolled 138 patients with bronchiectasis confirmed by high-resolution CT scans from July 2017 to August 2018. ResultsA total of 138 patients with bronchiectasis were enrolled. The data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Indian study reported 50% (7,8). This is higher than other areas of the world, even in Asia (Saudi Arabia 43%, Korea 20%) (5,6).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Indian study reported 50% (7,8). This is higher than other areas of the world, even in Asia (Saudi Arabia 43%, Korea 20%) (5,6).…”
Section: Discussionmentioning
confidence: 82%
“…Firstly, the frequency of Post TB Bronchiectasis (76% of all Bronchiectasis cases) is very high compared with other studies, even for South Asia. Notably a previous study from Southern Pakistan reported 58% and an Indian study reported 50%(7,8). This is higher than other areas of the world, even in Asia (Saudi Arabia 43%, Korea 20%)(5,6).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[36] A survey of post-TB bronchiectasis from India found that smoking prevalence was higher in post-TB bronchiectasis than in post-TB without bronchiectasis (27.27% vs. 12.12%). [37] Additionally, smokers could increase the risk of RBE in patients with autosomal dominant polycystic kidney disease. [38] Previous literature may explain the phenomenon that smoking increases the incidence rate of RBE, by which nicotine can increase the release of TNF-a, a key in ammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Sebuah penelitian menunjukkan bahwa kejadian bronkiektasis pasca infeksi tuberkulosis pada kelompok usia 31-40 tahun sebesar 21,74%, pada kelompok usia 41-50 tahun sebesar 23,19%, pada kelompok usia 51-60 sebesar 21,01%, dan pada kelompok usia >60 tahun sebesar 4,35%. 7 Studi kohort menunjukkan bahwa rata-rata usia pasien dengan penyakit obstruksi pasca tuberkulosis yaitu 51,8 tahun. 4 Penelitian lain menunjukkan temuan yang serupa yaitu usia rata-rata pasien dengan penyakit obstruksi pasca tuberkulosis adalah <65 tahun.…”
Section: Pembahasanunclassified